Spatial and temporal trend analysis of the burden of endocrine-related cancers among women of reproductive age in the Asia-Pacific region from 1990 to 2021: results based on the GBD study - Xia, Chengchi; Wang, Baoqing (Frontiers in Oncology, 2026)
BackgroundEndocrine-related cancers pose an escalating challenge for reproductive-age women in the Asia-Pacific region, characterized by persistent socioeconomic disparities.MethodsUsing data from the Global Burden of Disease Study 2021, we analyzed the incidence, mortality, and DALYs of breast, ovarian, and thyroid cancers across 15 countries (1990–2021). Trends were quantified using EAPC, and mortality trajectories through 2050 were projected using GAM.ResultsBreast cancer exhibited a polarized pattern: mortality steadily declined in High-SDI nations but surged in Low-SDI regions. Thyroid cancer revealed a dichotomy of screening-driven overdiagnosis in High-SDI settings versus high lethality in Low-SDI areas. Ovarian cancer maintained the poorest prognosis in resource-limited settings. Crucially, primary risk drivers are shifting from traditional behavioral factors to metabolic factors.ConclusionWith disparities projected to widen by 2050, stratified interventions are urgent. We recommend screening de-escalation for High-SDI nations and resource-adapted measures for Low-to-Middle SDI nations to bridge the growing equity gap. reproductive-age women.